Population redistribution in optically trapped polar molecules - Deiglmayr, Johannes; Repp, Marc; Dulieu, O.; Wester, R.; Weidemüller, Matthias (The European physical journal. D, Atomic, molecular, optical and plasma physics, 2011)
We investigate the rovibrational population redistribution of polar molecules in theelectronic ground state induced by spontaneous emission and blackbody radiation. As amodel system we use optically trapped LiCs molecules formed by photoassociation in anultracold two-species gas. The population dynamics of vibrational and rotational states ismodeled using an ab initio electric dipole moment function and experimental potentialenergy curves. Comparison with the evolution of the v″ = 3 electronicground state yields good qualitative agreement. The analysis provides important input toassess applications of ultracold LiCs molecules in quantum simulation and ultracoldchemistry.
Gesehen am 03.05.2022